2022
DOI: 10.21203/rs.3.rs-2324280/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between PAPP-A levels determined during the first trimester and birth weight at full-term.

Abstract: Introduction: Foetal birth weight is an important determinant of perinatal health. For this reason, various methods have been investigated for estimating this weight during pregnancy. Aims: The aim of this study is to evaluate the possible relationship between full-term birth weight and PAPP-A levels determined during the first trimester as part of combined screening for aneuploidy carried out in pregnant women. Material and methodology We carried out a single-centre study including pregnant women who were bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the article published by Turrado Sánchez et al, it was found that as the level of PAPP-A decreases, the birth weight also decreases [23].…”
Section: Amirgholami Et Almentioning
confidence: 97%
“…In the article published by Turrado Sánchez et al, it was found that as the level of PAPP-A decreases, the birth weight also decreases [23].…”
Section: Amirgholami Et Almentioning
confidence: 97%